Clinical features of secondary pulmonary alveolar proteinosis associated with myelodysplastic syndrome: Two case reports. Issue 44 (November 2017) - Liu, Yin; Chen, Lu Lu; Qiu, Yu Ying; Xiao, Yong Long; Cai, Hou Rong
Abstract: Rationale: Pulmonary alveolar proteinosis (PAP) is a rare lung disorder characterized by the abnormal accumulation of alveolar surfactant protein in alveolar spaces. Secondary PAP can result from myelodysplastic syndrome (MDS). Patient concerns: But most reports described a single case; here we reported 2 cases of PAP secondary to MDS. One case developed secondary PAP at the same time as MDS, and the other developed during the course of MDS. Diagnoses: The diagnosis of PAP was made by bronchoalveolar lavage and based on the identification of periodic acid-Schiff-positive proteinaceous material. Chest high resolution CT (HRCT) scans showed variable distribution of ground glass opacities, but crazy-paving appearance was not seen in our 2 cases. Interventions: Because the patients' general conditions were poor, whole lung lavage was not used in the 2 cases. Outcomes: And the 2 cases' prognoses were poor. Lessons: In conclusion, pulmonary physicians should suspect the possibility of secondary PAP when they encounter unexplained pulmonary infiltrates with some hematologic or infectious disease that shows diffuse bilateral GGO on an HRCT scan.